2018
DOI: 10.3389/fnmol.2018.00244
|View full text |Cite
|
Sign up to set email alerts
|

From Neural Crest Development to Cancer and Vice Versa: How p75NTR and (Pro)neurotrophins Could Act on Cell Migration and Invasion?

Abstract: The p75 neurotrophin receptor (p75NTR), also known as low-affinity nerve growth factor, belongs to the tumor necrosis factor family of receptors. p75NTR is widely expressed in the nervous system during the development, as well as, in the neural crest population, since p75NTR has been described as ubiquitously expressed and considered as a neural crest marker. Neural crest cells (NCCs) constitute an transient population accurately migrating and invading, with precision, defined sites of the embryo. During migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 117 publications
0
22
1
Order By: Relevance
“…Also, RhoA, Rac1 and Cdc42 have been implicated in both Eph/ephrin internalization and signaling. Eph/ephrin signaling plays essential roles during migration of neural crest cells, such as cytoskeleton remodeling and axon guidance but also stimulate angiogenesis and tissue separation (Baker and Antin, 2003; Xu and Wilkinson, 2013; Wislet et al, 2018). High expression levels of Ephb6 and its ligand ephrin-B2 and ephrin-B3 is associated with low-stage neuroblastoma (Tang et al, 2000).…”
Section: Potential Factors For Neuroblastoma Tumorigenesismentioning
confidence: 99%
“…Also, RhoA, Rac1 and Cdc42 have been implicated in both Eph/ephrin internalization and signaling. Eph/ephrin signaling plays essential roles during migration of neural crest cells, such as cytoskeleton remodeling and axon guidance but also stimulate angiogenesis and tissue separation (Baker and Antin, 2003; Xu and Wilkinson, 2013; Wislet et al, 2018). High expression levels of Ephb6 and its ligand ephrin-B2 and ephrin-B3 is associated with low-stage neuroblastoma (Tang et al, 2000).…”
Section: Potential Factors For Neuroblastoma Tumorigenesismentioning
confidence: 99%
“…An efficient method was described for the generation of NCCs from human pluripotent stem cells through the sustained activation of Wnt signaling combined with low Smad signaling, accomplished by the inhibition of the Activin/Nodal pathway. After 12 days, this constant inhibition of Smad considerably inhibited the formation of CNS Pax6 (OMIM 607108)-positive cells and increased the percentage of cells positive for the low affinity neurotrophin receptor, p75 NTR , which is expressed in the migratory NC (Heuer et al, 1990;Wislet et al, 2018). Within the population of p75 positive cells, authors found cells with intermediate levels of p75, but positive for Pax6; in contrast, the cell population that expresses high levels of p75 was positive for Ap-2α (OMIM 107580), characteristic of NCCs (Menendez et al, 2011).…”
Section: Wnt Signalingmentioning
confidence: 99%
“…NCSCs delaminate from the neuroepithelium by epithelial-to-mesenchymal transition (EMT) and migrate along body axes. Migrating neural crest (NC) cells lose the expression of E-cadherin (CDH1) and gain expression of human natural killer-1 (HNK1)/3-beta-glucuronosyltransferase 1 (B3GAT1), CD271, and endothelin receptor type B (EDNRB) [ 13 , 14 ] ( Figure 1 a). The expression of CD271 enables the tracking of NCSCs during early human NC development and the isolation of multiple NCSCs from mammalian fetal peripheral nerve and differentiated human embryonic stem cells (hESCs) [ 12 , 13 , 15 ].…”
Section: Cd271 In Developmentmentioning
confidence: 99%
“…First insight into the functional role of CD271 in cell migration was provided by murine models, which enabled the conditional knockout of CD271 in NC cells. The latter revealed a decrease in the sciatic nerve diameter and a deficiency of hematopoiesis, reviewed by Wislet et al [ 14 ]. Although the role of CD271 during melanocyte development and specification ( Figure S1a , comprehensively reviewed by Douarin et al, White et al and Blake et al [ 19 , 24 , 25 ] is unknown, knockdown studies in melanoma revealed a close relationship of CD271 with FOXD3, SOX2, and SOX10.…”
Section: Cd271 In Developmentmentioning
confidence: 99%
See 1 more Smart Citation